PELATIHAN PENGGUNAAN SISTEM INFORMASI BAGIAN UMUM SEKRETARIAT DAERAH KABUPATEN OGAN ILIR - Yulianingsih, Evi; Maria Ulfa; Wydyanto; Fatoni; Mutiara Yudita, (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
The General Affairs Division of the Regional Secretariat of Ogan Ilir Regency holds significant responsibility in managing government-owned assets, such as inventory items, operational vehicles, and buildings. Previously, the borrowing and returning processes for these assets were conducted manually using logbooks, leading to various issues such as recording delays, data loss risks, and difficulties in reporting and monitoring. Based on these conditions, this community service project aimed to design and implement a web-based Information System for Borrowing Inventory Items, Vehicles, and Buildings to enhance efficiency, transparency, and accuracy in asset management. The methods used in this project included direct observation on-site, system requirements analysis, UI/UX and database design, application development using PHP and MySQL, and functional system testing. The activity was carried out over a period of four months with a systematic sequence of phases, from data collection to the preparation of the final report.